The Auxiliary Role of Heparin in Bone Regeneration and its Application in Bone Substitute Materials - Wang, Jing; Xiao, Lan; Wang, Weiqun; Zhang, Dingmei; Ma, Yaping; Zhang, Yi; Wang, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Bone regeneration in large segmental defects highly depends on the action of osteoblasts and the ingrowth of new blood vessels. Therefore, it is particularly important to promote the production of osteogenic/angiogenic growth factors. Since the discovery of heparin, its anticoagulant, anti-inflammatory and anti-cancer functions have been extensively investigated during the past 100 years. Especially, its effects on bone regeneration have been studied, that long-term use of heparin is detrimental to bone regrowth. However, with the extensive application of heparin in orthopedics, its positive osteogenic effect has been gradually unveiled. About one-third of the transforming growth factor (TGF) superfamily is bound to heparin and heparan sulfate, among which TGF-β1, TGF-β2 and bone morphogenetic protein (BMP) are the most common ones. Heparin improves the delivery and retention of BMP-2 in vivo, which is used to promote the healing of large bone defects at extra-physiological doses. Heparin can also improve blood vessel formation, an integral part of fracture healing, by cooperating with platelet-derived growth factor (PDGF). In addition, heparin, as a binding agent of good growth factor and release component in nanomaterials, can significantly facilitate the controlled-release and retention of growth factors (such as fibroblast growth factor (FGF), BMP, PDGF, etc.) in vivo. Owing to these Material scaffold or delivery system composed of heparin and a variety of biomaterials (including organic, inorganic, metal, natural polymer, etc.) is very important for material bone regeneration. This paper reviews the structural properties and functions of heparin, with emphasis on bone regeneration under physiological conditions and its application in biomaterials.